Diabetic nephropathy in patients with type 2 diabetes mellitus and its correlation with diabetic retinopathy - Benevides Damasceno, Márcia; Martins Ferreira, Juliana de Lucena; da Silva Rodrigues, Raquel Ádria; Rodrigues Riedel da Costa, George (Journal of Health & Biological Sciences, 2024)
Objective: the present study aimed to evaluate the prevalence of diabetic nephropathy and diabetic retinopathy, in addition to the associations that can be established between these microvascular complications of diabetes mellitus. Methods: this was a retrospective study, a systematic review without meta-analysis. The authors used the Pubmed and SciELO databases to search the terms “diabetic nephropathy”, “diabetic retinopathy” and “type 2 diabetes”, including publications dated 2011 to 2021. Results/Discussion: the results presented were a synthesis of patients with both pathologies and their correlations, in addition to associated laboratory changes and agreement between the stages or severity of both conditions. Conclusions: DN and DR are pathologies that are directly interconnected and cause repercussions for patients.